Analisis Glikoprotein dalam Daging Mytilus viridis, Anadara granosa, dan Anadara maculosa - Zuhelmi Aziz; Thamrin Wikanta; Tirta Subagio (Fakultas Farmasi Universitas Pancasila, 2007)
Mussels is known to have ability living in clean or polluted waters environment due to it has a specific immunity system. The immunity mechanism is carried out by a glycoprotein that play role as an immunomodulator with high activity. Extraction of glycoprotein from fresh green mussel (Mytilus viridis), blood mussel (Anadara granosa) and bulu mussel (Anadara maculosa) have been carried out, by boiling the mussels for 30 minutes and 60 minutes, precipitation of glycoprotein with ethanol, then purification of glycoprotein through the Sephadex G-100 column. The amino acids composition of the glycoprotein was analyzed by high performance liquid chromatography (HPLC) with normal phase pico tag column, using 1 ml/min isocratic elution with sodium acetate buffer-acetonitril mixture, and detection with UV detector. Result showed that the yield of glycoprotein from 60 minutes boiling was higher than from 30 minutes boiling. The glycoprotein content of green mussel, blood mussel and bulu mussel were 11,97%, 8,36%, and 18,93% from 60 minutes boiling, and 10,32%, 7,93%, and 9,07 from 30 minutes boiling, respectively. It can be concluded that the amino acids composition in the glycoprotein from both treatment were not proportional , but the 60 minutes boiling was given higher result.